EVALUATION IN VITRO DIFFERENT FUNGICIDES FOR GROWTH OF RHIZOCTONIA BATATICOLA - A.M. KADAM,,; S.S. CHAVAN,; .H. KENDRE, (The Bioscan, 2020)
The present study was conducted to test the efficacy of some systemic, non-systemic and combine fungicides like Propiconazole, carbendazim, captan, carboxin, benomyl, mancozeb, thiram, carbendazim + mancozeb against dry root rot of chickpea. A variant with no application of fungicide was used as control. In laboratory condition result revealed that fungicides evaluated against R.bataticola exhibited a wide range of mycelial growth of R. bataticola and was found to be decreased drastically and showed inhibition with increased concentration of fungicides tested. The suppression of growth of pathogen was maximum with Carbendazim (Bavistin 50%WP) (100.00 per cent) followed by Benomyl (Benlate 50 WP) (93.61 (75.35)) per cent) and the least effective fungicides was Carboxin (Vitavax 75 WP) (61.17 (51.45) per cent). Carbendazim (Bavistin 50%WP) showed best performance against the pathogen.